E-105 Distal transradial access for targeted spinal angiography and embolization. (23rd July 2022) - Eesa, M; Lewkonia, P; Mitha, A
Abstract : Background: Spinal catheter angiography is indicated in the evaluation and treatment of spinal vascular lesions. The typical approach to spinal angiography consists of access through the femoral artery with the use of suitably shaped catheters for selective catheterization of the spinal segmental vasculature. We describe our experience with distal transradial access through the 'anatomical snuffbox' for targeted spinal angiography, to evaluate and treat selected vascular lesions in eight patients. Methods: A retrospective review of patients who underwent transradial spinal angiography and embolization was performed from August 2019 to January 2022. A total of Eight patients were identified, who underwent targeted spinal angiography through distal transradial access. Results: Seven patients had vascular tumors of the spinal column and underwent tumor embolization followed by segmental artery occlusion prior to surgery. One patient had a spinal dural AV fistula that could not be embolized due to feeding vessel tortuosity and eventually went on to have a laminectomy for disconnection of the fistula. None of the patients required conversion to femoral access. Mean total Fluoroscopy time was 31.4 minutes in the transradial angiography group compared to 35.9 minutes when similar procedures were performed by femoral access (n=9) during the study period. There were no access site hemorrhagic complications. One patient experienced transient mild hand numbness during the period of hemostasis with the vascular compression device that resolved completely within 24 hours. There were no instances of radial artery occlusion. Conclusion: Distal transradial access is a feasible and safe option for targeted spinal angiography and treatment in selected patients. This may be used as an option in patients in whom femoral occlusive disease precludes traditional femoral arterial access. Disclosures: M. Eesa: None. P. Lewkonia: None. A. Mitha: None.